2014
DOI: 10.1098/rstb.2013.0490
|View full text |Cite
|
Sign up to set email alerts
|

What are you doing? How active and observational experience shape infants' action understanding

Abstract: From early in life, infants watch other people's actions. How do young infants come to make sense of actions they observe? Here, we review empirical findings on the development of action understanding in infancy. Based on this review, we argue that active action experience is crucial for infants' developing action understanding. When infants execute actions, they form associations between motor acts and the sensory consequences of these acts. When infants subsequently observe these actions in others, they can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 137 publications
(184 reference statements)
6
78
0
1
Order By: Relevance
“…Considering that 14-to 16-month-old infants have well-established first-person experience with crawling but limited experience with walking, such data support the hypothesis presented above, that motor resonance may be modulated by first-person motor experience (van Elk, van Schie, Hunnius, Vesper, & Bekkering, 2008). A number of behavioral, electrophysiological, and brain-imaging studies converge on this interpretation (Calvo-Merino, Grèzes, Glaser, Passingham, & Haggard, 2006;Cross, Hamilton, & Grafton, 2006;Kanakogi & Itakura, 2011;Turati et al, 2013; for a review, see Hunnius & Bekkering, 2014).…”
supporting
confidence: 60%
“…Considering that 14-to 16-month-old infants have well-established first-person experience with crawling but limited experience with walking, such data support the hypothesis presented above, that motor resonance may be modulated by first-person motor experience (van Elk, van Schie, Hunnius, Vesper, & Bekkering, 2008). A number of behavioral, electrophysiological, and brain-imaging studies converge on this interpretation (Calvo-Merino, Grèzes, Glaser, Passingham, & Haggard, 2006;Cross, Hamilton, & Grafton, 2006;Kanakogi & Itakura, 2011;Turati et al, 2013; for a review, see Hunnius & Bekkering, 2014).…”
supporting
confidence: 60%
“…We gave ample space in this special issue to this topic [18][19][20][21][22]. It is highly debated whether the mirror system arose as the consequence of association learning or an evolutionary process that endowed a population of neurons with a mechanism necessary for accomplishing a specific function [20,23].…”
mentioning
confidence: 99%
“…First, through experience as actors, infants come to understand the world they experience in terms of potential actions. Thus, learning to perform novel actions should improve infants' capacity to predict the outcome of observed actions (Hunnius and Bekkering 2014;Meltzoff 2007;Woodward 2013). As evidence for this, several studies showed that infants' sensitivity to the target-directedness of an action correlates with their capacity to perform the very same action (Brand et al 2015;, and improves together with it .…”
Section: Social Cognition In Infancy Without Mindreadingmentioning
confidence: 99%